Developing affective brand commitment through voice assistants - Berrincha, Ana Margarida Banhudo (2020)
The development of artificial intelligence (AI) devices, such as voice assistants, has been growing, and with that comes a growing curiosity about this matter. The objective of this research was to identify possible mediators between the experience a customer has with the brand and the willingness to use a voice assistant, as well as being able to verify what could be the possible outcomes of using the AI device and how it could impact the relationship between the customer and the brand. With the usage of a Google Assistant, an experiment was recorded and shared online, through a website on a platform called Wix, where different scenarios were simulated to allow the reach of relevant conclusions. By conducting this experiment, it was concluded that independently from the experience the customer had, or did not had, with the brand, the usage of voice assistants is highly influenced by the level of familiarity with the brand. It was also concluded that the usage of voice assistants can lead to feelings of compassion and love towards the brand, which can consequently lead to an affective commitment with the brand. In a time were managers in any industry are working for ways to improve and maintain their relationships with the customers, the present research shows how technology is a crucial part of any marketing action, even when using an AI device to strengthen customer brand relationships.